Extraction of natural resources in contexts of abundance and scarcity: An experimental analysis on non-compliance with quotas in management and exploitation areas of benthic resources in central-southern Chile - Santis, Oscar; Chávez, Carlos (Estudios de Economía, 2014)
We study through framed field economic experiment the effects of exogenous changes in abundance levels of a renewable natural resource on compliance individual decisions of users operating under a common property regime and a system of Territorial use rights in fisheries (TURF) considering extraction quotas and external enforcement to detect and sanctions violations. Our results indicate that in the presence of resource abundance, fishermen decrease the level of abstraction when they face a quota external control vis-à-vis a common property regime, while in a situation of resources scarcity observed also a reduction in extraction levels; however, in this case fishermen have levels of non compliance and extractions higher than in the scenario of resource abundance, even with extractions above the Nash equilibrium.